Replication of twelve association studies for Huntington's disease residual age of onset in large Venezuelan kindreds. Issue 1 (3rd October 2006) - Andresen, J M; Gayán, J; Cherny, S S; Brocklebank, D; Alkorta-Aranburu, G; Addis, E A; Cardon, L R; Housman, D E; Wexler, N S
Abstract : Background: The major determinant of age of onset in Huntington's disease is the length of the causative triplet CAG repeat. Significant variance remains, however, in residual age of onset even after repeat length is factored out. Many genetic polymorphisms have previously shown evidence of association with age of onset of Huntington's disease in several different populations. Objective: To replicate these genetic association tests in 443 affected people from a large set of kindreds from Venezuela. Methods: Previously tested polymorphisms were analysed in the HD gene itself ( HD ), the GluR6 kainate glutamate receptor ( GRIK2 ), apolipoprotein E ( APOE ), the transcriptional coactivator CA150 ( TCERG1 ), the ubiquitin carboxy-terminal hydrolase L1 ( UCHL1 ), p53 ( TP53 ), caspase-activated DNase ( DFFB ), and the NR2A and NR2B glutamate receptor subunits ( GRIN2A, GRIN2B ). Results: The GRIN2A single-nucleotide polymorphism explains a small but considerable amount of additional variance in residual age of onset in our sample. The TCERG1 microsatellite shows a trend towards association but does not reach statistical significance, perhaps because of the uninformative nature of the polymorphism caused by extreme allele frequencies. We did not replicate the genetic association of any of the other genes. Conclusions: GRIN2A and TCERG1 may show true association with residual age of onset for Huntington's disease. The most surprising negative result is for the GRIK2 (TAA)n polymorphism, which has previously shown association with age of onset in four independent populations with Huntington's disease. The lack of association in the Venezuelan kindreds may be due to the extremely low frequency of the key (TAA)16 allele in this population.